Implementasi Electronic Customer Relationship Management pada Aplikasi Layanan Pelanggan Hotel - Wildan, Muhammad; Juanita, Safitri (P3M Politeknik Negeri Cilacap, 2022)
The interest of hotel visitors has decreased since the Covid-19 pandemic. So it is recommended that hotels implement Customer Relationship Management (CRM) which has three stages: getting new customers (Acquire), improving customer relationships (Enhance), and retaining customers (Retain). However, hotels currently do not have practical service applications that help to maintain the relationship between hotel management and consumers, so it requires research that implements E-CRM by designing a prototype of web-based Hotel customer service applications. This study aims to standardize hotel customer service applications that implement E-CRM. It uses qualitative research methods by applying the prototype system development method. The research contribution is to make an E-CRM prototype in a hotel customer service application with several features such as complaints, testimonials, promotions, and point redemption. Based on experiments and testing from a user using UAT and interview, the implementation of E-CRM using a prototype of web-based Hotel customer service applications helps the staff to find customer complaints. The promotion feature helps staff add promotional information that appears on the website's front page. Hotel customers can use the feedback feature in complaints, testimonials and redeem points exchange with prizes. In future research, sentiment analysis on hotel customer reviews using a classification algorithm can be carried out.